Low-energy density and high fiber intake are dietary concerns in female endurance athletes - Melin, A.; Tornberg, Å. B.; Skouby, S.; Møller, S. S.; Faber, J.; Sundgot-Borgen, J.; Sjödin, A. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Low or reduced energy availability (LEA) is linked to functional hypothalamic oligomenorrhea/amenorrhea (FHA), which is frequently reported in weight-sensitive sports. This makes LEA a major nutritional concern for female athletes. The aim of this study was to describe dietary characteristics of athletes with LEA and/or FHA. Endurance athletes (n = 45) were recruited from national teams and competitive clubs. Protocols included gynecological examination, body composition, eating disorder evaluation, and 7-day dietary intake and EA assessment. Athletes with disordered eating behavior/eating disorders (n = 11), menstrual dysfunction other than FHA (n = 5), and low dietary record validity (n = 4) were excluded. Remaining subjects (n = 25) were characterized by EA [optimal: = 45 kcal (188 kJ)/kg fat-free mass (FFM)/day (n = 11), LEA: < 45 kcal (188 kJ)/kg FFM/day (n = 14)] and reproductive function [eumenorrhea (EUM; n = 10), FHA (n = 15)]. There was no difference in EA between FHA and EUM subjects. However, FHA and LEA subjects shared the same dietary characteristics of lower energy density (ED) [(P = 0.012; P = 0.020), respectively], and fat content [(P = 0.047; P = 0.027), respectively]. Furthermore, FHA subjects had a lower intake of carbohydrate-rich foods (P = 0.019), higher fiber content (P < 0.001), and drive for thinness score (P = 0.003). Conclusively, low ED together with high fiber content may constitute targets for dietary intervention in order to prevent and treat LEA and FHA in female athletes.